Coastal States Powers In preventing epidemic foreign cruise ships by Covid19 from berthing at their ports - Cheriet, Souheila; Bouhouche, Hicham (Journal of Human Sciences, 2021)
The Covid 19 pandemic caused great panic for the international community, where it affected all regions of the world, by land, air and sea, and showed many deficiencies that must be corrected to face future epidemics, as international bodies and organizations stood helpless and satisfied with recommendations and directives, even if the stone was Health is an alternative measure imposed by all countries in the absence of a specific recommended vaccine that limits the spread of this dangerous virus. Humans have stayed at their homes and means of transport of all kinds are parked, but the sea monsters remain lost hanging in the water, with thousands of infected passengers on their back, It is the tragedy of the affected cruise ships, after coastal states closed their ports to maritime navigation and to preserve public health, they refused to receive them.